Variations in the Obesity Gene “LEPR” Contribute to Risk of Type 2 Diabetes Mellitus: Evidence from a Meta-Analysis - Ming Ming Yang; Jun Wang; Jiao Jie Fan; Tsz Kin Ng; Dian Jun Sun; Xin Guo; Yan Teng; Yan-Bo Li (Journal of Diabetes Research)
Leptin is a hormone protein regulating food intake and energy expenditure. A number of studies have evaluated the genetic effect of leptin (LEP) and leptin receptor (LEPR) genes on T2DM. This study aimed to investigate the association between these gene polymorphisms and T2DM by a systematic review and meta-analysis. Published studies were identified through extensive search in PubMed and EMBASE. A total of 5143 T2DM cases and 5021 controls from 14 articles were included in this study. Five functional variants in LEPR were well evaluated. Meta-analysis showed that rs1137101 (p.R223Q) was significantly associated with T2DM in all genetic models: allele model (OR = 1.27, 95% confidence interval (CI) = 1.13–1.42), dominant model (OR = 1.19, 95% CI = 1.05–1.35), homozygote model (OR = 1.82, 95% CI = 1.38–2.39), and recessive model (OR = 1.75, 95% CI = 1.35–2.28), with minimal heterogeneity and no indication of publication bias. Similar associations with T2DM were also found for rs62589000 (p.P1019P) and 3′UTR ins/del, although the data was obtained from a small number of studies. For the other two polymorphisms rs1137100 (p.R109K) and rs8179183 (p.K656N), they were not significantly associated with T2DM. Our results provide robust evidences for the genetic association of rs1137101 (p.R223Q) in LEPR with T2DM susceptibility.